Prevalence and Cytological Patterns of Cervical Lesions in Libyan Women: A Five-Year Pap Smear Analysis (Razi Medical Journal, 2025)
Cervical cancer remains a leading cause of morbidity and mortality among women, particularly in low-resource settings where preventive measures are limited. The Papanicolaou (Pap) smear test is recognized as the most effective screening tool for early detection of cervical lesions. This study aimed to assess the prevalence and cytological patterns of cervical abnormalities among Libyan women attending the gynecological outpatient department at the National Oncology Institute, Sabratha, between 2008 and 2012. A total of 669 cervical smears were analyzed and compared with findings from direct visual inspection. The results revealed significant discrepancies between visual examination and Pap smear outcomes, with the latter demonstrating superior sensitivity in identifying inflammatory and premalignant changes. Inflammation was the most common finding, followed by cervical intraepithelial neoplasia (CIN I and II), with higher rates observed among women over 40 years and those with high parity. Despite the known association between human papillomavirus (HPV) and cervical cancer, HPV detection remained low, reflecting limited diagnostic access during the study period. The findings support the implementation of national screening strategies and targeted health education to improve awareness, participation, and early detection. Future research should focus on evaluating specific screening models through prospective studies to optimize cervical cancer prevention across the country.
Keywords: Cervical Cancer, Pap Smear Screening, Cytological Abnormalities, Libyan Women